Soil Erosion in Humid Regions: A Review. (April 2015) - Holz, Daniel J.; Williard, Karl W.J.; Edwards, Pamela J.; Schoonover, Jon E.
Abstract Soil erosion has significant implications for land productivity and surface water quality, as sediment is the leading water pollutant worldwide. Here, erosion processes are defined. The dominant factors influencing soil erosion in humid areas are reviewed, with an emphasis on the roles of precipitation, soil moisture, soil porosity, slope steepness and length, vegetation, and soil organisms. Erosion dynamics in forested watersheds are the focus with some examples from agricultural watersheds included as well. Lastly, best management practices for controlling surface erosion are discussed.